INTERNATIONAL EXPERIENCE OF ASSESSING THE QUALITY OF BANKING ASSETS IN THE CONTEXT OF A RISK-BASED APPROACH - TARASEVYCH, Natalia; KARIMOV, Kirill (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article examines the international experience of assessing the quality of bank assets in the context of a risk-oriented approach. It is noted that the quality of the assets of a banking institution can be defined as information about the properties and parameters of assets that ensure stable and reliable functioning of the bank as a system that allows for development, adaptation to internal and external changes in the market environment, and to perform certain functions in the country's economy. It was determined that the processes of integration in the banking sphere, the use of the latest technologies, prompt the need to improve the existing and create new systems for evaluating bank assets and regulating the relevant risks of the bank. It is substantiated that the processes of liberalization of economic relations increase the pressure on the development of international standards of banking activity and the possibilities of their implementation in Ukraine. It was determined that when analyzing the parameters of the quality of bank assets in accordance with the functional approach, it is advisable to take into account such criteria as liquidity, riskiness, profitability of the bank, which reflect the main characteristics of the assets. It is noted that the assessment of the quality of the bank's assets has a comprehensive nature, which takes into account not only the financial aspects of the bank's activity, but also the quality of the business environment, corporate governance and dependence on market conditions. According to the results of the research, the concept of implementing a risk-oriented approach to asset quality assessment is proposed. Based on the assessment of banks according to this methodology, the control strategy is substantiated, including the need for early intervention mechanisms; the "viability" of the banking institution based on a one-year forecast and the sustainability of the bank's strategy for three years; the adequacy of the bank's own capital and the level of liquidity for risk management.
Keywords: asset quality; banking institutions; liquidity; riskiness; profitability; risk-oriented approach